Perlindungan Hukum Terhadap PPAT dalam Sistem Hak Tanggungan Elektronik (HT-el) - Amalia Rafi Ridha, Firly (Faculty of Law, Universitas Brawijaya, 2024)
The provision of Article 10 Paragraph (2) of the Regulation of Agrarian and Spatial Planning Minister/National Land Agency Number 5 of 2020 concerning Electronically Integrated Mortgage Right (henceforth referred to as HT-el) states that the submission of the supplementary documents must come with a statement letter highlighting the responsibility for the validity and the authenticity of the documents submitted. This written statement must be sent by a Land Deed Official (henceforth referred to as PPAT) as a part of registration and mortgage right transfer services. In case of any fake documents, as set forth, the PPAT must be responsible for this condition. This provision is taken as a burden for PPAT since there is a possibility that such a document falsification may be committed by another party, contrary to the provision requiring the PPAT to take the responsibility. This research employed statutory and conceptual approaches. The legal materials were analyzed based on systematic interpretation and analogy as a legal construction. The analysis results show that two different legal measures can be considered by PPAT; first, the protection within the scope of civil law represents internal legal protection received by PPAT from an agreement between PPAT and a client, while the external legal protection involves a defense and legal aid; second, the protection within the scope of criminal law represents preventive protection governed in Article 3 letter f of Code of Conduct of PPAT that takes into account the prudential principle. This principle is applied by PPAT during a deed-making process and registration process of the mortgage right, while the repressive legal protection involves legal aid, and a refusal right and obligation.